Unintentional injuries among children admitted in a tertiary care hospital in North Kerala - Akbar Sheriff; Asma Rahim; M P Lailabi; Jibin Gopi (Wolters Kluwer Medknow Publications, 2011)
World Health Organization global disease update (2004) points out injuries as the sixth leading cause of morbidity and mortality in childhood. A descriptive hospital based study was conducted to find out the common types of unintentional injuries among children admitted for management of unintentional injuries in Pediatric Surgery department and Intensive Care Unit of a tertiary care hospital of North Kerala and to find out the contributing risk factors. A total of 400 children admitted during the study period of 6 months of 2009 constituted the study population. Mechanical injuries comprising of Road traffic accidents and accidental fall were the major cause of unintentional injuries (36%), followed by Poisoning (22.3%). A higher proportion of unintentional injuries were noted to occur among children of younger mothers, overactive child, children belonging to extended or joint families, child left alone or with friends, pre-school children, male child and from urban dwellings. The study highlights the need to identify the different types of unintentional injuries and the risk factors of childhood injuries which require hospitalisation. Identification of risk factors will help to formulate strategies aimed at risk reduction and prevention of childhood injuries.